The Influence of Work Posture and Work Duration on the Incidence of Low Back Pain Among Batik Artisans: a Cross-sectional Study: Work Posture and Work Duration - Pamungkas, Megistra; Pratama, Susilo Budi; Fatharani, Lukman Faishal (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2024)
Background: Batik artisans, particularly those involved in the "nyanting" process, are susceptible to lower back pain due to non-ergonomic working postures. These craftsmen sit for long durations as they meticulously apply wax to fabric. They utilize dingklik, which compels them to sit in a slightly hunched position. The repeated adoption of such postures can heighten the risk of lower back pain. This research aims to investigate the relationship between work posture, years of service, and the incidence of low back pain among "nyanting" batik artisans in Pulorejo Village Methods: This observational analytical research employed a cross-sectional approach with 42 "nyanting" batik artisans chosen through a total sampling technique. Conducted in Pulorejo Village in January 2024, the research assessed work posture using the Rapid Entire Body Assessment (REBA) instrument, while the occurrence of low back pain was evaluated through history taking and physical examination. Statistical analysis was performed using IBM SPSS version 25.0 software. Results: A significant positive correlation was found between years of service and the occurrence of low back pain (LBP) (p=0.002; r=0.471). The risk of LBP increases with the length of service. Additionally, there was a significant positive correlation between working posture, as indicated by the REBA score, and the occurrence of LBP (p=0.010; r=0.395). A higher REBA score corresponds to a greater risk of LBP. Conclusions: the Years of service and the working posture were associated to  the incidence of low back pain (LBP) among "nyanting" batik artisans in Pulorejo Village.